1981
DOI: 10.1007/bf00198973
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic changes of a murine lymphoma by in vivo treatment with triazene derivatives

Abstract: ancer l mmunologyand i l lnmunotherapy © Springer-Verlag 1981 Summary. Five aryltriazenes were studied for efficacy in mediating immunogenic changes of tumor cells by in vivo treatment of lymphoma-bearing mice. It was found that four analog compounds produced increase in cell immunogenicity similar to that described for 5-(3,3-dimethyl-l -triazeno)-imidazole-4-carboxamide (DTIC), one of the five being by contrast completely inactive. Moreover, the use of a drug-resistant lymphoma illustrates that cytotoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In this paper we report on the metastatic properties of BL6 cells treated with the mutagenic compound potassium p-(3-methyl-l-triazeno)benzoate (MM-COOK), a xenogenizing chemical of the triazene class [6,16,17] for which no D NA hypomethylating activity can be demonstrated, and show that decreased metastatic ability may I" To whom correspondence should be addressed. be an early indication of the immunogenic changes associated with xenogenization by this type of compound.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we report on the metastatic properties of BL6 cells treated with the mutagenic compound potassium p-(3-methyl-l-triazeno)benzoate (MM-COOK), a xenogenizing chemical of the triazene class [6,16,17] for which no D NA hypomethylating activity can be demonstrated, and show that decreased metastatic ability may I" To whom correspondence should be addressed. be an early indication of the immunogenic changes associated with xenogenization by this type of compound.…”
Section: Introductionmentioning
confidence: 99%
“…The term chemical xenogenization indicates the production of stable cell variants with increased immunogenicity by exposure of tumor cells to chemicals acting as mutagens and/or gene activators [7,24]. The highly immunogenic sublines which result from mutagenesis of murine lymphomas with triazene derivatives [13,14] express new individual antigens, recognized by syngeneic cytotoxic T cells (CTL), that have been termed drug-mediated tumor antigens (DMTA) [6]. These antigens account for the decreased transplantability of the tumor variants resulting from xenogenization, and have been extensively characterized in in vivo and in vitro studies of cell-mediated immunity [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…laboratory have shown that treatment of murine lymphomas with triazene derivatives leads to alterations in immunogenicity, a phenomenon referred to as chemical xenogenization (Bonmassar et al, 1970;Fioretti, 1975;Fioretti et al, 1981), by analogy with the term first introduced by Kobayashi et al (1969). Each of the chemically xenogenized tumors is known to carry a distinctive set of drug-mediated tumor antigens (DMTA, Bonmassar et al, 1979), not detectable in the parental line, which make the xenogenized tumor antigenically foreign to the host of origin, thus causing the latter to resist challenge with high inocula of the drug-altered lymphoma (Bonmassar et al, 1972).…”
mentioning
confidence: 99%